Cyberpreneurial Mindset as a Driver of Digital Startup Success in Emerging Digital Economies - Danny Manongga; Ivan Kovac; Muhtarom Muhtarom (Pandawan Sejahtera Indonesia, 2026)
The rapid expansion of the digital economy has intensified competition among digital startups, yet high failure rates indicate that technological access alone is insufficient to ensure long-term success. While prior studies emphasize digital innovation and technological capability, limited research explains how the cyberpreneurial mindset functions as a strategic intangible resource that drives sustainable startup performance. Grounded in the Resource-Based View (RBV) and Dynamic Capability Theory (DCT), this study investigates how cyberpreneurial mindset dimensions of digital adaptability, opportunity recognition, innovation orientation, and calculated risk-taking contribute to digital startup success through the mediating role of strategic agility. This research addresses the gap concerning the cognitive behavioral foundations of digital entrepreneurial performance in emerging digital ecosystems. A quantitative approach was em- ployed using survey data collected from founders and top managers of digital startups. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and mediating relationships among constructs. The findings demonstrate that cyberpreneurial mindset significantly influences digital startup success, particularly through digital adaptability and innovation orientation. The study concludes that cyberpreneurial mindset rep- resents a valuable, rare, and inimitable intangible resource that strengthens a startup’s dynamic capabilities, enabling firms to sense, seize, and transform opportunities in volatile digital environments. This research contributes theoretically by integrating RBV and Dynamic Capability Theory into cyberpreneurship literature and provides managerial implications for digital entrepreneurs seeking sustainable growth in emerging economies.